Constrained Probabilistic multi-source Continuous Review Inventory Model with Dagum and Kumaraswamy-Dagum distributions - Fergany, Hala Ali; Alghamdi, Amani Saeed; Almutairi, Amsha Zayed (Arab Journal for Sciences and Research Publishing, 2023)
The main objective of this paper is to minimize the expected total cost using Lagrange multiplier approach with decreasing varying holding cost for probabilistic continuous review single-item multi-source inventory model under a restriction on the storage space. The optimal order quantity and the optimal reorder point for the best source which achieve the goal when lead time demand follows Dagum and Kumaraswamy-Dagum distributions of obtained. Also, an application is analyzed and reach the goal of minimizing the expected total cost with simulation data.
Keywords: Continuous Review; Lagrange multiplier technique; Storage space; decreasing varying holding cost; Dagum and Kumaraswamy -Dagum distributions